2016
DOI: 10.4306/pi.2016.13.6.583
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Therapy: A Prospective Treatment for Alzheimer's Disease

Abstract: Alzheimer's disease (AD) without cure remains as a serious health issue in the modern society. The major neuropathological alterations in AD are characterized by chronic neuroinflammation and neuronal loss due to neurofibrillary tangles (NFTs) of abnormally hyperphosphorylated tau, plaques of β-amyloid (Aβ) and various metabolic dysfunctions. Due to the multifaceted nature of AD pathology and our limited understanding on its etiology, AD is difficult to be treated with currently available pharmaceuticals. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 99 publications
(101 reference statements)
0
12
0
Order By: Relevance
“…Thus, NSC-based therapy for AD could provide a suitable neural microenvironment to inhibit neurodegeneration and to sustain the survival of mature neurons (Xuan et al 2009). However, they are limitations to NSCs such as failure to improve Aβ pathology, limited differentiation capacities to generate sufficient numbers of NSCs and cholinergic neurons, unwanted generation of non-neuronal cell types, and uncontrolled differentiation into glial cell types (Xuan et al 2009;Ager et al 2015;Lee et al 2016). Moreover, NSC content in the human brain declined with age (Manganas et al 2007).…”
Section: Stem Cell-based Therapy For Admentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, NSC-based therapy for AD could provide a suitable neural microenvironment to inhibit neurodegeneration and to sustain the survival of mature neurons (Xuan et al 2009). However, they are limitations to NSCs such as failure to improve Aβ pathology, limited differentiation capacities to generate sufficient numbers of NSCs and cholinergic neurons, unwanted generation of non-neuronal cell types, and uncontrolled differentiation into glial cell types (Xuan et al 2009;Ager et al 2015;Lee et al 2016). Moreover, NSC content in the human brain declined with age (Manganas et al 2007).…”
Section: Stem Cell-based Therapy For Admentioning
confidence: 99%
“…As demonstrated in AD animal models, transplanted stem cells have the potential to improve several cellular functions, such as synaptic connectivity (Blurton-Jones et al 2009), neurogenesis (Kim et al 2015), microglial activity (Yang et al 2013), angiogenesis (Garcia et al 2014), mitochondrial function (Zhang et al 2015b), and autophagy (Shin et al 2014). Therefore, stem cell transplantation could represent a promising and safe approach to treat AD, as it affects this disease through multiple mechanisms that result in re-building the neural integrity and improving the neurocognitive function (Fang et al 2018;Lee et al 2016;Choi et al 2014a). However, it has been suggested that engrafted stem cells are not the sole source of the newly generated neurons (Sullivan et al 2015;Zhang et al 2013).…”
Section: Induction Of Endogenous Neurogenesis (Neurogenic Potential)mentioning
confidence: 99%
“…At the same time it would be reasonable to implement some new therapies promoting the replenishment of neurons. [1][2][3][4][5][6][7][8][9] We are not the first who pay attention to SC as a promising way of anti-AD therapy. PubMed search for "stem cell Alzheimer's disease" on May-06-2018 returned 1839 scientific articles, most of them published within the recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we suggest local administration of MSC into submucosa of nasal cavity allowing their natural perineural migration to the target regions. 6,10,11 In this context, a wide range of different methods of cell therapy should be tested: embryonic SC, induced pluripotent SC, MSC-all these cells have positive potential in the treatment of patients with AD. 2,7,9,12 Positive effect of SC's neurotrophic function is well known: they release cytokines, growth factors and other signaling molecules (BDNF, NGF, IGF-1, VEGF) in damaged brain regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation